Outcomes of a “hospital at home” programme for the supervised home recovery of COVID-19 patients in Singapore - Michelle Woei Jen Tan; Mary Grace Aller Arciga; Juweita Binte Arba’in; Rachel Marie Towle; Su-Fee Lim; Woon Hoe Tang; Lian Leng Low (Proceedings of Singapore Healthcare, 2023)
Background The Singapore General Hospital COVID-19 Virtual Ward is a “hospital at home” (HaH) programme for the supervised home recovery of higher-acuity COVID-19 patients from the hospital and the community. Objective To describe how an existing HaH programme was redesigned so that COVID-19 patients could be remotely monitored at home and report the outcomes of the first 100 patients in this Virtual Ward. Methods Patients received an admission package comprising instructions and equipment for home monitoring, and uploaded their parameters into a clinical dashboard via a secure messaging app. Medical staff conducted video or telephone consultations daily. Patients were discharged according to time-based criteria, although some required SARS-CoV-2 PCR testing, which were conducted at home by a third-party medical provider. De-identified data of the first 100 patients were analysed by demographic details, indication for enrolment into the Virtual Ward, and the need for subsequent inpatient readmission. Results Of the first 100 patients admitted into the Virtual Ward, 58 were female, mean age was 63.1 years old (23–95 years), and 76 were fully vaccinated. There were 77 hospital referrals and 23 community referrals. The number of days of inpatient hospitalisation avoided was 717 days (average of 7.9 days per patient). Three hospital referrals (3.9%) were readmitted, while seven community referrals (30.4%) required subsequent hospitalisation. Conclusion The Virtual Ward programme demonstrates that selected COVID-19 patient can safely recover at home with remote medical support and monitoring, thereby expanding hospital capacity.